Comparative Morphological and Symptomatic Analysis of Alternaria alternata Disease in Green Gram (Vigna radiata) Across Six Districts in Rajasthan - Tak, Pooja; Agrawal, Kailash; Abhinav (Journal of Neonatal Surgery, 2025)
This study investigates the morphological and symptomatic characteristics of Alternaria alternata causing leaf spot disease in green gram (Vigna radiata) across six districts in Rajasthan—Jodhpur, Nagaur, Ganganagar, Ajmer, Bikaner, and Jaipur—during the Kharif seasons of 2022 and 2023. The research aims to provide a comprehensive analysis of the variation in disease symptoms, fungal morphology, and growth patterns in different geographical locations. Infected green gram leaves were collected from selected fields and subjected to surface sterilization and isolation on Potato Dextrose Agar (PDA) for fungal culture. The macroscopic and microscopic features of A. alternata isolates, including colony color, texture, conidia shape, and septation, were examined. Symptomatic observations focused on the development and severity of leaf spot symptoms in relation to environmental factors. The findings highlight the variability in disease expression across districts, with significant differences in colony morphology and disease severity. This comparative study offers valuable insights into the regional dynamics of Alternaria alternata in green gram cultivation, providing essential data for more targeted disease management strategies in Rajasthan.